Penerapan Sanksi Pelaku Tindak Pidana Penodaan Agama Berdasarkan Undang-Undang No 1 Tahun 2023 (International Forum of Researchers and Lecturers, 2024)
The Criminal Code is a body of laws that precisely governs how people behave in order to foster national development and alignment with state objectives, particularly for the Indonesian populace. One of the many tribes, nations, races, faiths, and civilizations that make up Indonesia is that it maintains the diversity of religious views among its citizens. There are believers of their own faiths in different parts of Indonesia, however the religions included in Presidential Determination Number 1 of 1965 are Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism. The existence of Law Number 1 of 2023 is controversial because there is legal ambiguity regarding the form and basis of sanctions against perpetrators of religious blasphemy or beliefs. As a result, their rights have not yet been granted and there is no basis for legal regulations. The study's objective is to ascertain the criminal penalties that, under Law Number 1 of 2023, are meted out to those who commit acts of religious blasphemy as well as the legal foundations for those who do so. It is possible to determine the types of criminal penalties that are given to offenders of religious blasphemy under Law Number 1 of 2023 by using a normative juridical approach.